2000
DOI: 10.1007/s002530050031
|View full text |Cite
|
Sign up to set email alerts
|

Lead, copper and zinc biosorption from bicomponent systems modelled by empirical Freundlich isotherm

Abstract: The biosorption of lead, copper and zinc ions on Rhizopus arrhizus has been studied for three single-component and two binary systems. The equilibrium data have been analysed using the Freundlich adsorption model. The characteristic parameters for the Freundlich adsorption model have been determined and the competition coefficients for the competitive biosorption of Pb(II)-Cu(II) at pH 4.0 and 5.0, and Pb(II)-Zn(II) at pH 5.0 have been calculated. For the individual single-component isotherms, lead has the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The maximum adsorption capacities (q max ) for Cu 2 þ on MC, CER and AC were found to be 53.19, 89.29 and 5.82 mg/g, respectively (Table 1). For Freundlich isotherm, the adsorption intensity (1/n) reflects the system suitability, and the adsorption is considered to be favourable when 1/n , 1 (Sag et al, 2000). In the present work, 1/n ¼ 0.29, which indicated the adsorption of Cu 2 þ by MC was favourable.…”
Section: Adsorption Isothermsmentioning
confidence: 51%
“…The maximum adsorption capacities (q max ) for Cu 2 þ on MC, CER and AC were found to be 53.19, 89.29 and 5.82 mg/g, respectively (Table 1). For Freundlich isotherm, the adsorption intensity (1/n) reflects the system suitability, and the adsorption is considered to be favourable when 1/n , 1 (Sag et al, 2000). In the present work, 1/n ¼ 0.29, which indicated the adsorption of Cu 2 þ by MC was favourable.…”
Section: Adsorption Isothermsmentioning
confidence: 51%
“…The co-presence of multiple metal cations elicited inhibitory effects in the cation binding process, stemming from the competition for binding sites on both bacterial cell surfaces and extracellular polymeric substances (EPS). It has been reported that in solutions containing multiple metals, some of the metal cations already bound on the EPS exert a strong hindrance to the access of other cations at the adjacent adsorption sites ( Sag et al, 2000 ; Micheletti et al, 2008 ; Pradhan and Rai, 2011 ; Lu et al, 2021 ). This steric effect results in EPS conformational change ( Huang et al, 2022 ) that leads to the general reduction in metal removal.…”
Section: Discussionmentioning
confidence: 99%